Bringing the hospital to the patient: first treatment of stroke patients at the emergency site. - Walter, S; Kostpopoulos, P; Haass, A; Helwig, S; Keller, I; Licina, T; Schlechtriemen, T; Roth, C; Papanagiotou, P; Zimmer, A; Viera, J; Vierra, J; et al. (Public Library of Science, 2010)
BACKGROUND: Early treatment with rt-PA is critical for favorable outcome of acute stroke. However, only a very small proportion of stroke patients receive this treatment, as most arrive at hospital too late to be eligible for rt-PA therapy. METHODS AND FINDINGS: We developed a "Mobile Stroke Unit", consisting of an ambulance equipped with computed tomography, a point-of-care laboratory system for complete stroke laboratory work-up, and telemedicine capabilities for contact with hospital experts, to achieve delivery of etiology-specific and guideline-adherent stroke treatment at the site of the emergency, well before arrival at the hospital. In a departure from current practice, stroke patients could be differentially treated according to their ischemic or hemorrhagic etiology even in the prehospital phase of stroke management. Immediate diagnosis of cerebral ischemia and exclusion of thrombolysis contraindications enabled us to perform prehospital rt-PA thrombolysis as bridging to later intra-arterial recanalization in one patient. In a complementary patient with cerebral hemorrhage, prehospital diagnosis allowed immediate initiation of hemorrhage-specific blood pressure management and telemedicine consultation regarding surgery. Call-to-therapy-decision times were 35 minutes. CONCLUSION: This preliminary study proves the feasibility of guideline-adherent, etiology-specific and causal treatment of acute stroke directly at the emergency site.